THE IRONIC IMAGINATION : A Source for Christian moral life, Contribution of William F. Lynch, S.J. - Polisetti, Innaiah (Asian Horizons, 2011)
Our present generation is in a constant conflicting situation of values, and thus the society is divided into groups. The very notion of diversity of values makes it difficult for moral discussion. This is not mere a political and economical problem but also moral and spiritual one. The response and reasoning of the morally conscious person depends on his/her moral outlook, who wants to be related to the world around and the values one holds. For the best moral response the believer’s “world view” should be in line with that of Jesus Christ and His teachings found in the Gospels and in the Tradition of the Church.